Pengendalian Kualitas Statistika Pada Pupuk ZA III di PT Petrokimia Gresik Menggunakan Maximum Half Normal Multivariate Control Chart (Max-Half-Mchart) - Salsabila, Nadia; Wibawati (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2024)
Max-Half-Mchart is one of the multivariate control diagrams that can monitor the average and variability of processes simultaneously or simultaneously. This diagram is a development of the Max-Mchat diagram with a half-normal distribution approach. This diagram is able to detect out of control signals well when there is a process shift. The data used in this study is data on the characteristics of ZA III product quality at PT Petrokimia Gresik. The quality control of ZA III Fertilizer at PT Petrokimia Gresik using Max-Half-Mchart shows that there is a shift in variability and average caused by the consistency of ( ) which is different in each production process, resulting in less than optimal products. Meanwhile, the overall production in the time period from October 2022 to September 2023 has been capable.